Talent management analysis of Indonesian civil advocates - Hendriarti, Susie Fitri; Othman, Norfaridatul Akmaliah; Arif, Sazelin; Syeh, Assery; Nur Jamal, Fauziyah (ASR Research India, 2022)
Studies of talent management are very rarely found until now. It will be very attractive if a comprehensive study is conducted to explore the talent management. In this study, 5 conceptual models will be developed and tested with the aim to find a full model (hybrid model) of talent management. The objectives of the research are: (1) to develop a Full Model (Hybrid Model) of Talent Management based on 5 proposed conceptual models are Soft Skill Model, Hard Skill Model, Competency Model, Performance Model, and Success Model. And (2) to predict the relationships between variables in the 5 conceptual models proposed and 1 full model (hybrid model) developed. This research was conducted in the context of Indonesian Civil Advocates. The sample was taken of 100 advocates selected purposively in 5 big cities are Medan, Yogyakarta, Jakarta, Makassar, and Banjarmasin. A quantitative approach using the survey method was conducted to test models and hypotheses developed. Data Analysis was used Partial Least Square (PLS) to accommodate Variance-Based Structural Equational Modelling (VB-SEM). The findings are as follows. Soft Skills has no influence on Talent Management. Hard Skills has a positive influence on Talent Management. Competency has a positive influence on Talent Management. Performance has a positive influence on Talent Management. Success has a positive influence on Talent Management. This study would help in achieving effective talent management in the context of Indonesian civil advocates. The result of this study would contribute to the Strategic Human Resource Management (SHRM) body of knowledge. The results obtained from this study would provide information to Indonesian civil advocates that are essential for the practice of Indonesian civil advocates to assist them in their careers.